Self-reported musculoskeletal pain, headache, jaw pain and swallowing dysfunction in a sample of young Saudi adults who stutter - Almudhi, Abdulaziz; Zafar , Hamayun (Journal of the Pakistan Medical Association, 2023)
Objective: To report the prevalence of musculoskeletal pain, headache, jaw pain and difficulty in swallowing among people who stutter (PWS). Method: The cross-sectioal study was conducted from October 3, 2021, to March 21, 2022, after approval from the ethics review committee of King Khalid University, Abha, Saudi Arabia, and comprised adult people who stutter belonging to different regions of Saudi Arabia. They were divided into five groups based on stuttering severity as estimated by Stuttering Severity Instrument-4. Data was collected on musculoskeletal pain in different body areas using a questionnaire.. Data ws analysed using SPSS 22. Results: Of the 101 Arabic-speaking subjects, 63(62.4%) were males and 38(37.6%) were females. The overall mean age was 27+/7 years (range: 18-39 years). The largest group was of subjects with moderate severity of stuttering 31(30.6%); 21(68%) males and 10(32%) females. The increase in number of musculoskeletal pain locations was related to the severity of stuttering (p<0.05). The most common musculoskeletal pain sites were the lower back 31(31%), neck 26(26%) and shoulder 26(26%). Frequent headaches and difficulty chewing hard food due to jaw pain were reported by 49(49%) and 22(22%) participants, respectively (p<0.05). Swallowing difficulty was reported by 9(9%) participants (p>0.05). Conclusions: Widespread chronic musculoskeletal pain of low intensity was found to be common among people who stuttered, and the number of pain locations was positively related to stuttering severity. Key Words: Stuttering, Musculoskeletal pain, Headache, Jaw, Deglutition.